2008
DOI: 10.1007/s00431-008-0819-6
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated differences in prevalence of group A streptococcal type-specific M antibodies in children

Abstract: Our prior studies of the molecular epidemiology of group A streptococcus (GAS) pharyngitis indicated that the most common emm types associated with pediatric pharyngitis in North America were 12, 1, 28, and 4. We previously reported that the proportions of pediatric pharyngitis due to emm types 12 and 4 decreased with increasing age throughout childhood. We hypothesized that this is due to age-associated acquisition of antibodies to the amino-terminal type-specific region of common GAS M proteins during childh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…The North American emm type data from 2000 to 2007 clearly confirm and extend our previous observation that the classic rheumatogenic types (3,5,6,14,18,19, and 29) have markedly decreased in prevalence, and in some instances completely disappeared, compared with their prevalence among pharyngeal types circulating in the 1960s when acute rheumatic fever was a common pediatric illness [3]. Of 8474 pharyngeal isolates in this study, only 1 emm type 14, 18 emm type 18, no emm type 19, and 15 emm type 29 isolates were recovered.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The North American emm type data from 2000 to 2007 clearly confirm and extend our previous observation that the classic rheumatogenic types (3,5,6,14,18,19, and 29) have markedly decreased in prevalence, and in some instances completely disappeared, compared with their prevalence among pharyngeal types circulating in the 1960s when acute rheumatic fever was a common pediatric illness [3]. Of 8474 pharyngeal isolates in this study, only 1 emm type 14, 18 emm type 18, no emm type 19, and 15 emm type 29 isolates were recovered.…”
Section: Discussionsupporting
confidence: 84%
“…We have also reported that several of the more common emm types account for a progressively lower proportion of pharyngeal isolates among older children and teenagers than in younger children, suggesting a role for typespecific immunity [17]. In support of this concept, recently Jaggi et al [18] reported that serum antibody levels to several common M proteins were higher in older than in younger children.…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, it has been reported that several of the most common emm types account for a progressively lower proportion of pharyngeal isolates among older children and adolescents compared to younger children, suggesting a role for type-specific immunity [39]. In addition, it has been reported that serum antibody levels to several common M proteins were higher in older than in younger children [40].…”
Section: Discussionmentioning
confidence: 99%
“…Serosurveys of antibodies against the clinical serology antigens, Streptolysin O (SLO) and DNAse B, in different age groups and in different countries and socioeconomic settings support an age-related increase in these antibodies which are believed to represent biomarkers of Strep A exposure 35 , 36 . There are different theories for how Strep A antibodies confer protection: (1) natural human immunity to Strep A infection is type-specific and directed against the M-protein 37 , so that repeated exposures to different M types (or emm -clusters 38 ) builds a repertoire of type-specific responses responsible for protection 39 ; and (2) responses accumulate with repeated exposures to conserved (non-M-protein) Strep A antigens, raising the threshold of protection against subsequent infection 40 , 41 . Measurements of antigen-specific antibodies following Strep A infections indicate antibodies against both type-specific and conserved antigens occur concurrently and both likely contribute to immunity 42 , 43 .…”
Section: Anti-strep a Antibodiesmentioning
confidence: 99%